Chemokine Receptor CXCR3 Correlates with Decreased M2 Macrophage Infiltration and Favorable Prognosis in Gastric Cancer. (21st May 2019) - Chen, Fangfang; Yuan, Jingping; Yan, Honglin; Liu, Huan; Yin, Shuai
Abstract : Aim . The aim of this study was to explore the correlation of chemokine receptor CXCR3 with M2 macrophage infiltration, various clinicopathological features, and prognosis in patients diagnosed with gastric cancer (GC). Methods . Expression of CXCR3 protein and M2 macrophage was evaluated in 156 GC patients and corresponding paracancerous tissues by immunohistochemical (IHC) analysis. Results . In our study, 59 (37.82%) showed high expression of CXCR3 protein in 156 GC tissues. Expression of CXCR3 protein was significantly increased in tumor tissues compared with corresponding paracancerous tissues ( P < 0.001). Overexpression of CXCR3 protein correlated with decreased M2 macrophage infiltration ( P = 0.001). By analyzing the association between expression of CXCR3 protein and clinicopathological factors of GC patients, we found that high level of CXCR3 protein was significantly correlated with better differentiation ( P =0.017), I/II TNM stage ( P = 0.02), and smaller invasion depth ( P = 0.003). Moreover, we found through Kaplan-Meier analysis and log-rank test that GC patients with high expression of CXCR3 protein and low M2 macrophage infiltration had better overall survival (OS) and low mortality rate ( P < 0.001 and P = 0.024, respectively). The multivariate survival analysis showed that high expression of CXCR3 protein could serve as a favorable independent biomarker for prognosis in GC patients [hazard ratio (HR): 0.342 (0.204-0.571); P < 0.001]. Conclusion . Our study indicates that overexpression of CXCR3 protein in GC is associated with decreased M2 macrophage infiltration and improved OS and thus can be further exploited as a biomarker in GC.